Pengaruh Pendapatan Orang Tua dan Gaya Hidup Terhadap Perilaku Konsumsi Mahasiswa - Mahendra, Rafi Atha; Hanifa, Nurul (Universitas Negeri Surabaya, 2023)
Consumptive behavior is someone who tends to consume without limits that prioritizes emotional considerations rather than intellectual considerations or is more aligned with wants than needs. This study aims to determine the effect of parental income and lifestyle on the consumption behavior of FEB UNESA students. The analytical method used is a quantitative method. Linear regression with diagonal is the analytical technique used. The results of this study resulted that parents' income and lifestyle influenced the consumption behavior of FEB UNESA students.